711 Comparison Between Overweight/Obese (OW/OB) Patients: Coeliac vs Non Coeliac Ones. (October 2012) - Mercurio, R; Guttadoro, D; Podagrosi, M; Grimaldi, A; Barbato, M; Caiazzo, AM; Petrarca, L; Vania, A
Abstract : Background and Aims: In literature there are case reports of coeliac disease (CD) diagnosed in OW/OB children and studies assessing the body weight excess (EBW) at CD diagnosis. Besides, an incorrect gluten-free-diet (GFD) often leads to EBW. Aim of this study is to assess the effect of a balanced diet in coeliac patients (CP) with EBW compared to matched non-coeliac patients (NCP) with EBW. Methods: and results: In 2006–2010, we selected 8 (4M, 4F, age=11.35±3.79) out of 29 CP we follow; they all had EBW (z-BMI=1.93±0.69) and were compliant to the GFD. Follow-up lasted 11.62±1.68 months, with a z-BMI reduction in all cases (z-BMI=1.45±1.01). Among the matched 8 NCP (4M, 4F, age=10.52±3.60; start-up's z-BMI=2.07±0.59;), followed-up for the same period of time, 7 reduced their z-BMI (1.57±0.67), while in 1 it worsened. Conclusions: Despite the limited number of patients, our study underlines the importance of a strict supervision in CP with EBW to improve their nutritional status. We also noticed that the coherent adhesion to a balanced GFD and the consequent effect on z-BMI are better than those among NCP, probably because in CP the nutritional prescriptions are perceived as indispensable for the therapy of CD. Bibliografia: Mariani P et al. J Pediatr Gastroenterol Nutr 1998; 27:519–523; Polito C et al. Nutr Res 1992; 12:353–358; Rea F et al. J Pediatr Gastroenterol Nutr 1996; 23:408–412; Dickey W, Kearney N. Am J Gastroenterol 2006; 101:2356–2359; Aydogdu S et al. Dig Dis Sci 2009; 54:2183–2187; Patro B, Szajewska H. Curr Opin Clin Nutr Metab Care. 2010; 13:300–4.